2015
DOI: 10.1371/journal.pone.0117848
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Effects on Disease Onset and Lifespan of the Mutant Dynactin p150Glued Mouse Model of Motor Neuron Disease

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease primarily affecting motor neurons in the central nervous system. Although most cases of ALS are sporadic, about 5–10% of cases are familial (FALS) with approximately 20% of FALS caused by mutations in the Cu/Zn superoxide dismutase (SOD1) gene. We have reported that hSOD1-G93A transgenic mice modeling this disease show a more severe phenotype when the transgene is bred on a pure SJL background and a milder phenotype when bred on a pure B6 backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This gene is located on chromosome 12q13-q15, which is a region prone to stable amplification in many cancers. The DCTN family has been linked to neurodegeneration (14,15), and more and more studies have shown that DCTN2 may be a potential prognostic biomarker for cancer, including cutaneous melanoma, colon adenocarcinoma, and osteosarcoma (16)(17)(18). FK506-binding protein 14 (FKBP14) belongs to the FK506binding protein family.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is located on chromosome 12q13-q15, which is a region prone to stable amplification in many cancers. The DCTN family has been linked to neurodegeneration (14,15), and more and more studies have shown that DCTN2 may be a potential prognostic biomarker for cancer, including cutaneous melanoma, colon adenocarcinoma, and osteosarcoma (16)(17)(18). FK506-binding protein 14 (FKBP14) belongs to the FK506binding protein family.…”
Section: Discussionmentioning
confidence: 99%
“…DCTN1 is considered the largest subunit of dynactin, 23 and DCTN1 has been implicated in many neurodegenerative diseases. 10 12 DCTN2 connects with DCTN1 and DCTN3 to form a complex subunit. 23 DCTN4 was found to be associated with Wilson’s disease 24 and chronic Pseudomonas aeruginosa infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that the DCTN family is linked with multiple neurodegenerative diseases. 10 12 Nevertheless, after bibliographic retrieval, it was found that only a few studies stated the correlation between the DCTN family and the prognosis and diagnosis of COAD.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we examined the effects of different genetic backgrounds on amyloid deposition and various related molecular pathogenic markers in a transgenic model of ATTRV30M. Genetic background has previously been shown to affect the phenotype and severity of other neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) [15] , [16] , [17] . Considering that the two lines of mice used in the current study bear the same mutation with regards to the disease-causing locus, our results suggest that genetic modifiers affect disease progression, or in this case, amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%